Economics of Row spacing and Integrated weed management in soybean - Daramola, Olumide Samuel; Adeyemi, Olusegun Rapheal; Adigun, Joseph Aremu; Adejuyigbe, Christopher Olu (Journal of Agricultural Sciences (Belgrade), 2019)
High cost of cultivation and weed management is a major limiting factors to increased soybean productivity and net returns. Field experiments were conducted in 2016 and 2017 at the Teaching and Research Farm of Federal University of Agriculture Abeokuta to evaluate the economic performance of different of row spacing and integrated weed management system in soybean. Three row spacings (50, 75 and 100 cm) as the main plot treatments and six weed control methods and a weedy check as sub-plot treatments were accommodated in a split-plot arrangement of randomized complete block design with three replications. There was significant reduction in weed biomass with reduction in row spacing from 100 to 75 and 50 cm in both years. Furthermore, cost of production, grain yield and gross profit increased with reduction in row spacing from 100 to 75 and 50 cm in both years. When planted with 50 cm row spacing, application of propaben or butachlor at 2.0 kg a.i (active ingredient)/ha each followed by (fb) supplementary hoe weeding (shw) at 6 weeks after sowing (WAS) resulted in the highest yield (2301-2484 kg/ha) and total revenue (2129-1972 /ha). Conversely, three hoe weedings resulted in the highest yield (2155-2081 kg/ha) and total revenue (1848-1783 /ha) for crops grown at wide (75 and 100 cm) row spacings. Despite the higher yield and revenue obtained with three hoe weedings for crops grown at 75 and 100 cm row spacing, however, the gross profit and benefit-cost ratio obtained was lower than those obtained with herbicides treatments applied alone or fb shw. In terms of profitability, soybean planted at 50 cm row spacing and treated with probaben at 2.0 kg a.i/ha fb shw gave the highest gross profit of 1479/ha. Increasing the number of hoe weeding to two or three times in soybean planted at narrow (50 cm) row spacing did not guarantee highest yield, but rather increased the cost of weed control. This study suggests that narrow row spacing (50 cm) and pre-emergence herbicides will help to reduce the number of hoe weedings and consequently high cost of production required for optimum yield, and increase profitability in soybean production.